Car crash detector system: article / Mohd Shahril Mat Saad - Mat Saad, Mohd Shahril (2009)
This paper propose a new technology of the safety system that called car crash detector. The sensor will detect the impact of collision and send the signal to the system. The system will automatically turn off the engine if it met the condition which is in danger situation. This can avoid the car from burning or get exploded. The system also preventing the airbag from activated if the low impact collision occurs where the situation is not dangerous to driver then the airbag is no need to be activated. Programmable Interface Controller (PIC) is use as an interface between the input (sensor) and output (engine system). The system use distance detector or distance sensor type to detect the distance changes within interval of 3cm between radiator and front of the car's engine or can also shown between backs of the car's engine and sensor. The change of the distance that varies by speed is considered to make sure the correct programming code can be downloaded into the PIC. This paper also discuss on the programming using the assembly language and the flow of the system. The programming code more concern on the delay operation of the system and the Analog-to-Digital Converter (ADC). The delay used in this system is l .08ms and this delay operates to delay operation of reading the signal from input (sensor). Hardware for this project designed base on considering the distance by 8cm, 11 cm, and 14cm. The result of this project is discussed in three cases which are low, high, and very high impact collision.